Articulation between metrics and textual data as methodological experimentation for circulation studies (Intercom - Brazilian Journal of Communication Sciences, 2024)
This work’s objective was to experiment the possibilities of articulation between metrics and textual data in researches focused in circulation of meanings. This is an excerpt from a broader research on the circuits formed around the first three reports of the Vaza Jato series published by The Intercept Brasil, on June 9, 2020. To guide the discussion, we briefly mention some studies on circulation processes and we discuss Braga’s (2017) theoretical approach on the notion of communicational episodes. To show the possibilities of integration between metrics and the inferential perspective, as referred by the author, we present the episode named “Shameless”. It was through the observation of clues left by the digital tracks that we managed to make a connection between the quantitative data generated by software and the texts.